A Study of Mixed Vegetable Dyes with Different Extraction Concentrations for Use as a Sensitizer for Dye-Sensitized Solar Cells. (3rd July 2014) - Cho, Kun-Ching; Chang, Ho; Chen, Chih-Hao; Kao, Mu-Jung; Lai, Xuan-Rong
Abstract : Two vegetable dyes are used for the study: chlorophyll dye from sweet potato leaf extract and anthocyanin dye from extracts of blueberry, purple cabbage, and grape. The chlorophyll and anthocyanin dyes are blended in a cocktail in equal proportions, by volume. This study determines the effect of different extraction concentrations and different vegetable dyes on the photoelectric conversion efficiency of dye-sensitized solar cells. In order to make the electrode for the experiments, P25 TiO2 powder was coated on the ITO conducting surface, using a medical blade, to form a thin film with a thickness of around 35 μ m. The experimental results show that the cocktail dye blended using extracts of sweet potato leaf and blueberries, in the volumetric proportion 1 : 1, at a weight concentration of 40%, using an extraction temperature of 50 ° C and an extraction heating time of 10 min produces the greatest photoelectric conversion efficiency (η ) of up to 1.57%, an open-circuit voltage (V OC ) of 0.61 V, and a short-circuit current density (J SC ) of 4.75 mA/cm 2 .